Tratamento químico de sementes de soja: qualidade fisiológica, sanitária e potencial de armazenamento - Conceição, Gerusa Massuquini (2013)
Soybean is the main oilseed crop produced in the world, and many factors can affect the soybean yield, including the diseases and insects attacks. Thus, the seed treatment with fungicides and insecticides is another alternative for ensuring the establishment of appropriate plant stands in the field. In addition, is common the use of soybean seed coating with polymers to improve the incorporation of other products used in the seed treatment. Therefore, the aim of this study was to evaluate the physiological and health quality of soybean seeds treated with fungicide, insecticide, micronutrients and polymer. The study was developed in two chapters, being the first entitled "Physiological, and health quality and yield of soybean seeds with chemical treatment", which aims to evaluate the effect of soybean seed treatment on the physiological and health quality, as well as, on the field performance of seeds. In the second chapter, entitled "Soybean seeds chemical treatment on the physiological and health quality during storage" aimed to evaluate the effect of seed treatment with fungicide, insecticide micronutrients and polymer, during the storage period. The chemical treatment of soybean seeds is a suitable tool to improve the physiological performance of soybean seeds and the plants establishing in the field. Furthermore, the use of these products helped to maintain physiological and health quality of seeds during storage.